Water water everywhere and not a drop to drink, nor do i know its whereabouts - Dunne, Robert (2012)
The demand for water is driven primarily by population and concomitant economic growth. Water requirements are predicted to grow considerably in the next decades while supplies will remain relatively constant or decline due to over pumping of aquifers, changing weather patterns and increased water pollution and contamination. Mining activities are often located in remote, arid environments, with limited access to high-quality water. The water used in mining operations comes from a variety of sources and the sources and quality of the water varies from operation to operation. Mining impacts on water quantity and quality are among the most contentious aspects of mining development. The main problem for the mining industry is to generate confidence in developing a responsible, sustainable and transparent water management strategy that is recognized as such by all stakeholders. This paper provides an overview of water in the wider global arena and compares this to how the mining industry has dealt with water stewardship over the last couple of decades.